Potential Tracking OF Cytotoxic Activities Of Mangrove Perepate (Sonneratia alba) Root Extract as an Anticancer Candidate - Madyawati Latief; Nelson Nelson; Hilda Amanda; Indra Lasmana Tarigan; Siti Aisyah (Universitas Padjadjaran, Indonesia)
Mangrove plants are one of the most extensive biodiversity in Jambi. Besides functioning as a coastal ecosystem protector, it also has any potential of its chemical content. The study of mangrove’s bioactive compound is important to generate a new therapeutic agent. This study aims to obtain chemical compounds that have cytotoxic activity, reveal the chemical formula and molecular structure of that active compound, and determine the cytotoxic activity level of active compound from perepat (Sonneratia alba) root extract. The extract was isolated and purified using Liquid Vacuum Chromatography, Graphitation Column Chromatography, and Thin Layer Chromatography. The isolate was characterized using FT-IR spectrophotometry. Our result found that it corresponds to the β-sitosterol compound group with a high similarly chromophore. Furthermore, both of the extract and isolate was tested for toxicity activity using the Brine Shrimp Lethality Test (BSLT) method using Artemia salina shrimp larvae. Herein, we reported that acetone isolated extract possesses lower cell death average 100% (start 200 μg/ml) than isolate extract 80% (50μg/ml). Furthermore the toxicity of total extract has LC50 23,98 (μg/ml), while Isolate 10,04 (μg/ml). From the LC50 value, it can be concluded that the toxicity of the extract lower than the isolate, and both were classified as very toxic compounds, and very potential to be developed into anti-cancer drug compounds.